Design of the Alterable Arms-palm for Robotic Multi-fingered Hands - Li Jianhai; Zhang Qiuju (Jixie chuandong)
For the objects with different sizes and shapes,grasp planning and control problems of the robotic multi-fingered hands have not been solved perfectly till now. After summarizing varieties of the existing robotic palms,it is concluded that some novel palm structures can improve the dexterity and working space of the robotic multi-fingered hands,and make the structure and control simpler. Based on the analysis of the motion mechanism of the octopus arms,the generalized arms-palm structure is put forward,which can be configured to any size and shape of the polygon. Then a bionic robotic multi-fingered hand with 12 DOF is designed. In order to simplify the control and structure,a novel bionic palm structure with 5 DOF is proposed,named the alterable arms-palm. For the objects with different sizes and shapes,the alterable arms-palm will change into the suitable configuration of the palm,shifting the fingers to the optimal contact point locations on the objects. In this way,the dexterity and working space of the robotic multi-fingered hands are improved significantly by the alterable arms-palm. The configuration analysis shows that the adaptive palm-configuration of various sizes and shapes can be realized simply and rapidly by the alterable arms-palm,the grasp quality is improved and the complexity of grasp planning and control is reduced.